The Urgency of a Maintenance Statement Deed Made Before a Notary for Children Born Out of Wedlock as a Form of Ta'zir Against the Biological Father Based on Notarial Practice in Indonesia - Sari, Melia Putri Purnama (Universitas Islam Malang, 2024)
The status of children born out of wedlock carries significant consequences, especially for those who are not recognized. Recognition, which is sought through a petition in the District Court, is essential as it constitutes a form of legal protection. This effort affects the process of determining heirs and the provision of maintenance, particularly from the biological father. To ensure legal certainty, a maintenance statement deed is made before a notary as evidence for the future. This research uses a normative juridical method, employing data collection techniques from literature studies by analyzing core issues and sources from relevant legal products.